2021
DOI: 10.3390/ijerph182212221
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the COVID-19 Lockdown on the Position-Specific Match Running Performance of Professional Football Players; Preliminary Observational Study

Abstract: The COVID-19 pandemic interrupted professional football in the 2019/2020 season, and football experts anticipate that the consequences of lockdown measures will negatively affect the physical performance of players once competition restarts. This study aimed to evaluate position-specific match running performance (MRP) to determine the effect of COVID-19 lockdowns on the physical performance of professional football players. Players’ MRPs (n = 124) were observed in matches before and after the COVID-19 lockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
3
11
1
1
Order By: Relevance
“…A second limitation is that the training intensity was not monitored. Third, in soccer, aerobic power or endurance capacity differs according to playing positions due to the different tactical roles in the matches during the COVID-19 Lockdown [30]. In our study, the effect of detraining on aerobic capacity was not shown in terms of different playing positions.…”
Section: Discussioncontrasting
confidence: 63%
“…A second limitation is that the training intensity was not monitored. Third, in soccer, aerobic power or endurance capacity differs according to playing positions due to the different tactical roles in the matches during the COVID-19 Lockdown [30]. In our study, the effect of detraining on aerobic capacity was not shown in terms of different playing positions.…”
Section: Discussioncontrasting
confidence: 63%
“…In comparison to Norwegian soccer, the sprint distance of the first team under investigation corresponds most with those of central defenders or central midfielders at Level 1. Total distance as well as high-speed running observed for the first team in this study seem to be similar to what is known from the Croatian First Division 2019/20 season ( Sekulic et al, 2021 ).…”
Section: Discussionsupporting
confidence: 83%
“…Physical match performance in German Bundesliga mainly did not change significantly from pre to post COVID-19 break in 3 out of 3 studies, i.e., high-intensity running distance (0.61 ≤ p ≤ 0.70; 0.03 ≤ ES 0.05) and sprinting distance (0.20 ≤ p ≤ 0.82; 0.02 ≤ ES ≤ 0.09) [3,17,18]. In 1 out of 1 study for Polish Ekstraklasa (p ≤ 0.03; − 0.27 ≤ ES ≤ − 0.18), in 1 out of 1 study for Croatian HNL (p ≤ 0.04; − 1.42 ≤ ES ≤ 1.44), in 2 out of 3 studies for Spanish La Liga (p ≤ 0.017; − 0.32 ≤ ES ≤ 5.5), and in 1 out of 1 study for Italian Serie A (p ≤ 0.014; − 1.01 ≤ ES ≤ 0.24), most physical match parameters such as total distance and high-intensity running distance decreased from pre to post [4,17,[19][20][21]. 1 out of 3 studies for Spanish La Liga did not find significant differences in physical match performance, i.e., total distance, low-intensity running distance, high-intensity running distance, and sprinting distance (p = n. s.; ES = N/A), between pre-and post-COVID-19 break [22].…”
Section: Physical Match Performancementioning
confidence: 92%